2012
DOI: 10.1111/j.1600-0447.2012.01860.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercise through mountain hiking in high‐risk suicide patients. A randomized crossover trial

Abstract: The results suggest that a group experience of regular monitored mountain hiking, organized as an add-on therapy to usual care, is associated with an improvement of hopelessness, depression, and suicide ideation in patients suffering from high-level suicide risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 40 publications
5
49
1
3
Order By: Relevance
“…Two studies on young inpatients with mental disorders have examined suicidality changes as an outcome of exercise (Davidson et al, 2013;Sturm et al, 2012). One study revealed that exercise reduced suicidality in young inpatients with post-traumatic stress disorder (Davidson et al, 2013), and the other revealed that 9 weeks of hiking reduced suicidal ideation in patients at high risk for suicide (Sturm et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Two studies on young inpatients with mental disorders have examined suicidality changes as an outcome of exercise (Davidson et al, 2013;Sturm et al, 2012). One study revealed that exercise reduced suicidality in young inpatients with post-traumatic stress disorder (Davidson et al, 2013), and the other revealed that 9 weeks of hiking reduced suicidal ideation in patients at high risk for suicide (Sturm et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…For instance, future studies may examine whether longer interventions lead to more lasting benefits and whether benefits could be sustained more easily if extended group-based wilderness programs were paired with more regular single or half-day group-based nature recreation experiences. It may be particularly interesting to investigate whether combining outdoor recreation experiences with more conventional therapeutic approaches would lead to even larger and more substantial changes in well-being given recent studies exploring the effects of these types of programs on individuals with depression, TBI, and suicidal tendencies [51][52][53][54].…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Developed by Sturm et al (2012) 33 Today I felt that my environment was too crowded (not enough space or too many people).…”
Section: Likertmentioning
confidence: 99%
“…Developed by Sturm et al (2012) 34 Today, because of the temperature, I felt (cold/warm). Likert Spirituality Constructed by our research group, inspired by the item # 3 from the Self-Transcendence Scale of the Temperament and Character Inventory (Cloninger et al, 1993) 38 Today I felt a strong spiritual or emotional connection with all the people around me.…”
Section: Likertmentioning
confidence: 99%
See 1 more Smart Citation